The clock component OsLUX regulates rice heading through recruiting OsELF3-1 and OsELF4s to repress Hd1 and Ghd7 - Peng Xu; Yingxin Zhang; Xiaoxia Wen; Qinqin Yang; Ling Liu; Shulei Hao; Jiaxin Li; Zhaozhong Wu; Liaqat Shah; Amir Sohail; Qunen Liu; Lianping Sun; et al. (Journal of Advanced Research, 2023)
Introduction: Circadian clocks coordinate internal physiology and external environmental factors to regulate cereals flowering, which is critical for reproductive growth and optimal yield determination. Objectives: In this study, we aimed to confirm the role of OsLUX in flowering time regulation in rice. Further research illustrates how the OsELF4s–OsELF3-1–OsLUX complex directly regulates flowering-related genes to mediate rice heading. Methods: We identified a circadian gene OsLUX by the MutMap method. The transcription levels of flowering-related genes were evaluated in WT and oslux mutants. OsLUX forms OsEC (OsELF4s–OsELF3-1–OsLUX) complex were supported by yeast two-hybrid, pull down, BiFC, and luciferase complementation assays (LCA). The EMSA, Chip-qPCR, luciferase luminescence images, and relative LUC activity assays were performed to examine the targeted regulation of flowering genes by the OsEC (OsELF4s–OsELF3-1–OsLUX) complex. Results: The circadian gene OsLUX encodes an MYB family transcription factor that functions as a vital circadian clock regulator and controls rice heading. Defect in OsLUX causes an extremely late heading phenotype under natural long-day and short-day conditions, and the function was further confirmed through genetic complementation, overexpression, and CRISPR/Cas9 knockout. OsLUX forms the OsEC (OsELF4s–OsELF3-1–OsLUX) complex by recruiting OsELF3-1 and OsELF4s, which were required to regulate rice heading. OsELF3-1 contributes to the translocation of OsLUX to the nucleus, and a compromised flowering phenotype results upon mutation of any component of the OsEC complex. The OsEC complex directly represses Hd1 and Ghd7 expression via binding to their promoter's LBS (LUX binding site) element. Conclusion: Our findings show that the circadian gene OsLUX regulates rice heading by directly regulating rhythm oscillation and core flowering-time-related genes. We uncovered a mechanism by which the OsEC target suppresses the expression of Hd1 and Ghd7 directly to modulate photoperiodic flowering in rice. The OsEC (OsELF4s–OsELF3-1–OsLUX)–Hd1/Ghd7 regulatory module provides the genetic targets for crop improvement.